Characterization of exosomes derived from Toxoplasma gondii and their functions in modulating immune responses - Li Y (Dove Medical Press, 2018)
Yawen Li,1,* Yuan Liu,1,2,* Fangming Xiu,3 Jianing Wang,4 Hua Cong,1 Shenyi He,1 Yongyu Shi,4 Xiaoyan Wang,4 Xun Li,5 Huaiyu Zhou1 1Department of Pathogen Biology, School of Basic Medical Sciences, Shandong University, Shandong, People’s Republic of China; 2Clinical Laboratory, The People’s Hospital of Changle, Shandong, People’s Republic of China; 3Translational Medicine, SickKids Research Institute, the Hospital for Sick Children Toronto, OT, Canada; 4Department of Immunology, School of Basic Medical Sciences, Shandong University, Shandong, People’s Republic of China; 5Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Shandong University, Shandong, People’s Republic of China *These authors contributed equally to this work Introduction: Exosomes are nanograde membrane-bound vesicles secreted from most cell types through the fusion of multivesicular bodies with plasma membranes. Some of these exosomes are well defined, and are known to have immunomodulatory properties as well as play critical roles in intercellular communications. In this study, we characterized the exosomes derived from Toxoplasma gondii and their functions in aspect of immune responses.Methods: T. gondii exosomes were isolated and identified using electron microscopy, nanoparticle tracking analysis, and Western blotting. The viability of macrophage RAW264.7 cells affected by exosomes was evaluated using a Cell Counting Kit (CCK-8). Then the uptake of T. gondii exosomes by RAW264.7 cells was detected by labeling with fluorescent dye PKH67. After exosomes stimulation, in vitro the production of interleukin (IL)-12, tumor necrosis factor (TNF)-α, interferon (IFN)-γ and IL-10 in RAW264.7 cells were investigated using enzyme-linked immunosorbent assay (ELISA). In immunized BALB/c mice, the antibodies, cytokines as well as the percentage of CD4+ and CD8+ T cells were determined using ELISA and flow cytometric analysis. Protective efficacy was evaluated by challenging intraperitoneally with tachyzoites of T. gondii.Results: We successfully isolated and characterized the exosomes derived from T. gondii. Functionally, the viability of macrophage RAW264.7 cells was significantly affected by exosomes at a high concentration (160 µg/mL). The production of IL-12, TNF-α and IFN-γ in macrophage cells were increased, and the level of IL-10 was decreased. Furthermore, BALB/c mice immunized with T. gondii exosomes showed both humoral and cellular immune responses and also exhibited a prolonged survival time.Conclusion: T. gondii exosomes could modulate macrophage activation in vitro and trigger humoral and cellular immune responses and partial protection against acute parasite infection in mice, which suggested that exosomes may serve as a potential candidate against toxoplasmosis. Keywords: Toxoplasma gondii, exosomes, macrophage, mouse, immune response